Responses to Stress among East Malaysian Students : Psychometric Properties of the Responses to Stress Questionnaire - Lai, Hui Yee; Cheah, Whye Lian; Helmy, Hazmi; Ang, Ai Ling (Penerbit Universiti Sains Malaysia, 2023)
Background: Academic stress is part of a student’s life. Chronic stress may result in mental health problems, affecting the adolescent’s well-being in adulthood. However, not all types of stress result in a negative effect. Therefore, understanding how adolescents adapt to academic stress can lay the groundwork for preventive interventions. The Response to Stress Questionnaire (RSQ) for academic problems centred on a multidimensional model of responses to stress. However, it has not been tested among Malaysians. Thus, this study aimed to validate the questionnaire among Malaysians. Methods: The questionnaire was translated into the Malay language using forward and backward translation. Data were collected via self-administered questionnaires at a secondary school in Kuching. A validity test was conducted using face and content validation by subject matter experts, and construct validation was performed using exploratory factor analysis (EFA). A reliability test was conducted by checking Cronbach’s alpha. Results: Results showed that the questionnaire has good validity and reliability. The EFA resulted in only three dimensions of responses to stress among Malaysian adolescents in contrast to the five dimensions in the original RSQ for academic problems. The Cronbach’s alpha showed good reliability of the questionnaire. Conclusion: The questionnaire measuring responses to stress was valid and reliable in assessing the responses of adolescents to academic stress.